PENGARUH LOVE OF MONEY DAN GENDER TERHADAP NIAT MELAKUKAN PENGGELAPAN PAJAK - Alifia Dewi Kusuma Wardani; Mega Utami (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This study aims to examine the effect of love of money and gender on the intention to commit tax evasion. This study uses quantitative descriptive methods and primary data using a questionnaire. The population in this study were prospective taxpayers of the University of Sarjanawiyata Tamansiswa Yogyakarta with a total sample of 115 respondents. Sampling in this study used a snowball sampling technique. The data were analyzed using the IBM SPSS Statistics 20 program. The results of this study indicate that love of money has a positive effect on the intention to commit tax evasion, and gender has no effect on the intention to commit tax evasion.